Nickel-Catalyzed Three-Component Unsymmetrical Bis-Allylation of Alkynes with Alkenes: A Density Functional Theory Study - Tao Yu; Jingxuan Zhang; Guo Liu; Liangfei Duan; Kun V. Tian; Gregory A. Chass; Weihua Mu (Molecules, 2024)
Density functional theory (DFT) characterizations were employed to resolve the structural and energetic aspects and product selectivities along the mechanistic reaction paths of the nickel-catalyzed three-component unsymmetrical bis-allylation of alkynes with alkenes. Our putative mechanism initiated with the in situ generation of the active catalytic species [Ni(0)L2] (L = NHC) from its precursors [Ni(COD)2, NHC·HCl] to activate the alkyne and alkene substrates to form the final skipped trienes. This proceeds via the following five sequential steps: oxidative addition (OA), β-F elimination, ring-opening complexation, C-B cleavage and reductive elimination (RE). Both the OA and RE steps (with respective free energy barriers of 24.2 and 24.8 kcal·mol−1) contribute to the observed reaction rates, with the former being the selectivity-controlling step of the entire chemical transformation. Electrophilic/nucleophilic properties of selected substrates were accurately predicted through dual descriptors (based on Hirshfeld charges), with the chemo- and regio-selectivities being reasonably predicted and explained. Further distortion/interaction and interaction region indicator (IRI) analyses for key stationary points along reaction profiles indicate that the participation of the third component olefin (allylboronate) and tBuOK additive played a crucial role in facilitating the reaction and regenerating the active catalyst, ensuring smooth formation of the skipped triene product under a favorably low dosage of the Ni(COD)2 catalyst (5 mol%).